The teachers’ perception of professionalism development: during and post pandemic Covid-19 - Okky Leo Agusta; Jumiati Siska; Meydia Afrina; Rambat Nur Sasongko; Muhammad Kristiawan (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
Teachers’ professionalism development in post pandemic Covid-19 shifts to online activities because of use-technology adaptation during pandemic Covid-19. This study aims to portray teachers’ professionalism activities during and post Covid-19. This study employed a qualitative survey to gain 15 junior high school teachers’ opinion in Lubuklinggau with open-ended questions by online questionnaire. The data were analyzed based on interactive model of analysis including; data reduction, data display, conclusion drawing/verification and data collection from an interactive cyclical process. Teachers are insisted to be more active and creative to build effective learning process. Adaptation in using technology also affect teachers’ professionalism activities. Preference in online activities makes them to participate professionalism activities online cause of easiness and cost-effectiveness.